2016
DOI: 10.1016/j.jcps.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

“Every coin has two sides”: The effects of dialectical thinking and attitudinal ambivalence on psychological discomfort and consumer choice

Abstract: Prior research suggests that consumers experience psychological discomfort when they make a choice under attitudinal ambivalence. The research reported here examines systematic cross‐cultural variations in psychological discomfort as a function of dialectical thinking and attitudinal ambivalence in the context of choice. It shows that compared to nondialectical (Western) consumers, dialectical (Eastern) consumers experience less psychological discomfort when they hold bivalent evaluations of the focal object, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 52 publications
3
44
1
Order By: Relevance
“…A large body of research has examined how dialectical thinking impacts individuals' interpretations of a phenomenon and their affective, cognitive, and behavioral responses in a variety of contexts both within and across cultures, including conflict resolution (Peng & Nisbett, 1999), emotional experience (Choi & Nisbett, 2000; Hui et al, 2009; Spencer‐Rogers et al, 2010; Williams & Aaker, 2002), self‐concept (Choi & Choi, 2002; Spencer‐Rodgers et al, 2010), shopping experience (Shavitt & Barnes, 2020), and response to product information (DeMotta et al, 2016; Pang et al, 2017; Wang et al, 2016). Of particular relevance to the current research, prior studies have shown that dialectical thinking predicts greater acceptance of people being ever‐changing as well as possessing both favorable and unfavorable aspects.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…A large body of research has examined how dialectical thinking impacts individuals' interpretations of a phenomenon and their affective, cognitive, and behavioral responses in a variety of contexts both within and across cultures, including conflict resolution (Peng & Nisbett, 1999), emotional experience (Choi & Nisbett, 2000; Hui et al, 2009; Spencer‐Rogers et al, 2010; Williams & Aaker, 2002), self‐concept (Choi & Choi, 2002; Spencer‐Rodgers et al, 2010), shopping experience (Shavitt & Barnes, 2020), and response to product information (DeMotta et al, 2016; Pang et al, 2017; Wang et al, 2016). Of particular relevance to the current research, prior studies have shown that dialectical thinking predicts greater acceptance of people being ever‐changing as well as possessing both favorable and unfavorable aspects.…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…Second, research on ambivalent attitudes (Wang, Batra, and Chen 2016) reveals that when both positive and negative information about a product is accessible, attitudinal ambivalence toward that product can result. This attitudinal ambivalence in turn creates discomfort and affects consumers’ predispositions toward the ambivalent product (Pang et al 2017). Including both performance-related and emotional COO cues, our CIP model accounts for felt ambivalence and tests its potential role empirically.…”
Section: Conceptual Background and Model Developmentmentioning
confidence: 99%
“…Positive and negative emotions have been viewed as two ends of a continuum, and are considered mutually exclusive (e.g., Russell, 1989 ). Researchers have recently suggested that people can experience different emotions simultaneously, but of opposite valence (e.g., Cacioppo et al, 1999 ; Penz and Hogg, 2011 ; Pang et al, 2017 ). Ramanatham and Williams (2007) demonstrate that customers experience a mixture of emotions, both positive and negative, in response to indulgent consumption.…”
Section: Introductionmentioning
confidence: 99%
“… How can ambivalence or mixed consumption emotions be resolved? Olsen et al, 2005 ; Penz, and Hogg (2011) ; Otnes et al (1997) ; Pang et al (2017) ; Ruth et al (2002) What is the relationship between time and blended emotions? How can the association between these two perspectives be quantified?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation